THE FREEDOM OF CONTRACT IN PLANTATION CORE ESTATE AND SMALLHOLDERS - Ermanto Fahamsyah (Diponegoro Law Review, 2019)
The Plantation Core Estate and Smallholders (PIR/Perkebunan Inti Rakyat) is a partnership scheme of the estates whereby a large estate acts as the core of development to small local farms in a mutually beneficial, integral, and continous system. Simply put, PIR is one form of contract farming. The PIR scheme was first introduced in by Indonesia government in order to encourage the development in local farms. Moreover, the partnership system is based on patron-client relationship and regulated through a contract in which the large estate is the patron and local farms are the client. However, the PIR system involves state within the contract. The state’s involvement is important so as to safeguard the interests of local farms (client) which are prone to predatory exploitation by the patron (large estate) and thus, balancing the bargaining powers of each party in the contract. This paper problematizes the contractual mechanism of PIR in respect to the freedom of contract. Thus, it can be concluded that the state’s involvement in the PIR shows that the freedom of contract principles are rigged to a degree which restricts some of the patron’s powers such as controls on supply and price in order to protect the local farms from being exploited.